Parenting Style and Daily Language Used by Los Asmat Society - Agustinus Gereda; Rezky Uspayanti; Novi Indriyani; Seli Marlina Radja Leba (Jurnal Sinestesia, 2023)
The aim of this research to see the parenting style and daily language used by the society in Los Asmat, on Noari Street, Merauke city. This research was a kind of qualitative research. The subject participants were Los Asmat society from children until adult, the teacher or the church administration of Kalam Kudus School. In collecting the data, the researchers used observation and interview. Observations were made to the Los Asmat community, both children and parents with the aim of gathering information regarding the application of parenting styles and the language used in daily life. The observation was done in two steps namely the observation was done in Los Asmat village and observation in teaching and learning process at Kalam Kudus School. To make the data more valid, the researchers used interview with semi-structured interview which consisted of some questions. The interview was done in two steps. For the first step, interview was done twice by asking some question for the Los Asmat society about parenting style and language used while interview step 2 was given for the teacher or church administration of Kalam Kudus School to know deeply about the children language used of Los Asmat society. As the result, the parenting style used by the Los Asmat society, some of them send their children to the school but some of them did not send their children to school because of economy factors. For the language used in daily life, it was almost same with the people in general namely used Indonesian language and they can interact each other although some of them still difficult to use polite language. About the parenting style, there is a relationship between parenting style and children's language development. In parenting, the parenting style adopted by some parents is more democratic in nature, giving children the freedom to determine what is best for them with their parents still guiding them. Giving the example in how good habit and bad habit. Thus, the parents also be gentle especially for father in educated their children. But, this model mostly was found by the educated parents namely the parents who have any received education.